Family Language Policy: Maintaining an Endangered Language in the Home - Smith-Christmas, Cassie; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2016)
Based on an eight-year study of a family on the Isle of Skye, Scotland, this book explores why the children in the family do not often speak Gaelic, despite the adults' best efforts to use the language with them, as well as the children's attendance at a Gaelic immersion school.
Keywords: Linguistics; Comparative linguistics; Historical linguistics; Sociolinguistics; Language policy; Language and languages -- Study and teaching; Linguistics; Sociolinguistics; Language Teaching; Language Policy and Planning; Historical Linguistics; Comparative Linguistics; Electronic books